Soil CO2 efflux following rotary tillage of a tropical soil - La Scala, N.; Lopes, A.; Panosso, A. R.; Camara, F. T.; Pereira, G. T. (Elsevier B.V., 2005)
Stopping the increase of atmospheric CO2 level is an important task and information on how to implement adjustments on tillage practices could help lower Soil CO2 emissions would be helpful. We describe how rotary tiller use on a red latosol affected Soil CO2 efflux. The impact of changing blade rotation speed and rear shield position on soil CO2 efflux was investigated. Significant differences among treatments were observed up to 10 days after tillage. Cumulative CO2 efflux was as much as 40% greater when blade rotation of 216 rpm and a lowered rear shield was compared to blade rotation of 122 rpm and raised shield. This preliminary work suggests that adjusting rotary tiller settings could help reduce CO2 efflux close to that of undisturbed soil, thereby helping to conserve soil carbon in tropical environments. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: soil respiration; soil CO2 efflux; rotary tiller; Soil management; soil tillage systems